2001
DOI: 10.1021/la010289d
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior and Formation of Reverse Cubic Phase Based Emulsion in Water/Poly(oxyethylene) Poly(dimethylsiloxane) Surfactants/Silicone Oil Systems

Abstract: The phase behavior of long hydrophobic A−B type silicone surfactants, Me3SiO−(Me2SiO) m - 2−Me2SiCH2CH2CH2−O−(CH2CH2O) n H (Si m C3EO n ), in water and water + octamethylcyclotetrasiloxane (D4) was investigated by studying phase behavior and small-angle X-ray scattering. Si25C3EO15.8 forms a reverse micellar cubic phase (I2) in water and water + D4 systems. This cubic phase is highly thermally stable in a surfactant−water binary system. The thermal stability decreases monotonically with addition of silicone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 27 publications
6
52
0
Order By: Relevance
“…For NH140 oil + biosurfactant + water the temperature transition is reached at T = 80 °C, for surfactin concentration below 0.3 (above 0.4 the transition temperature decreases to 75 °C). This was also observed by Uddin et al (2001) in a phase diagram for a water-in-surfactant binary system (Si 25 C 3 EO 15,8 ).…”
Section: Behaviour Of Phase Diagramssupporting
confidence: 67%
“…For NH140 oil + biosurfactant + water the temperature transition is reached at T = 80 °C, for surfactin concentration below 0.3 (above 0.4 the transition temperature decreases to 75 °C). This was also observed by Uddin et al (2001) in a phase diagram for a water-in-surfactant binary system (Si 25 C 3 EO 15,8 ).…”
Section: Behaviour Of Phase Diagramssupporting
confidence: 67%
“…The emulsions formed, in both cases, were white, due to the difference between the internal and external phase refractive index, 6,16 highly viscous, stiff, and presented shear-thinning behavior and a yield stress depicts (Figure 1), and considering the components used, the structure of the liquid crystal is assumed to be reverse. Diluting the samples in cyclohexane, and not being able to dilute them in water, confirmed that the internal phase was indeed water.…”
Section: Formation and Stability Of W/i 2 And W/h 2 Gel Emulsionsmentioning
confidence: 99%
“…Due to an unfavorable direct contact between the hydrophilic part and oils, reverse micelles are usually formed when an amphiphile is added into nonpolar solvents. Reverse micelles are mostly observed in the ternary mixtures of surfactant/water/oil, mostly in oil rich regions [11][12][13] . Furthermore, they have also been observed in aqueous systems of lipophilic surfactant in surfactant rich regions 14,15 .…”
Section: Introductionmentioning
confidence: 99%